hello

i know that deriv(cscx) = -cscxcotx
and that
deriv(cos) = -sinx
deriv(cotx) = -((cscx)^2)
my question is:
is this (statements below) correct?
antideriv(cscxcotx) = -(cscx)
antideriv(sinx) = -cosx
antideriv((cscx)^2)= -cotx

were those antiderivatives above correct?
ALSO basically my question is how i can remember where the negative sign goes and with which trig funcation it goes with; also is this correct : to go from a derivative to an antiderivative, (visually) change the derivative symbol to an antiderivative symbol, then switch the places of the trig identities on either side of the equal sign (flipflop them), and keep the negative sign where it is....? is this right? thank you!

1 answer

1. THey are right.
2. How can you remember? Flash cards.
3. I don't like that rule, complicated. I just recommend memorizing the derivatives, when that is done, the inverse operation is easy. Flash cards.
Similar Questions
  1. hi!ok, i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -sinx deriv(cotx) = -((cscx)^2) my question is: is this
    1. answers icon 1 answer
  2. My previous question:Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
    1. answers icon 2 answers
  3. express in sinx1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so
    1. answers icon 0 answers
  4. express this in sinx(1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?? and B) express in cosx problem: is 1 +
    1. answers icon 1 answer
more similar questions